2013
DOI: 10.1051/0004-6361/201220743
|View full text |Cite
|
Sign up to set email alerts
|

Members of Centaurus OB1 and NGC 4755: new spectroscopic and astrometric studies

Abstract: Context. An OB association is a gravitationally unbound group of stars. The identification of the members of the association is an important aspect of its study. There are few astrometric membership studies for OB associations, but the combination of these studies with astrophysical techniques becomes a very powerful tool for this type of research. Aims. We perform new spectroscopic and astrometric studies of the members of the association Centaurus OB1 (Cen OB1) and the open cluster NGC 4755. Methods. To carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
6
8
0
Order By: Relevance
“…Our derived distance of 2.6 +0.4 −0.3 kpc is larger than the 2.3±0.4 kpc estimated by Negueruela et al (2011), but again consistent within the 1σ uncertainties. However, the distance estimate of Negueruela et al (2011) was based on the best previous determination of the distance to Cen OB1, which has recently been revised upwards to 2.6 ± 0.5 kpc (Corti & Orellana 2013). Hence our distance remains fully consistent with the PSR B1259−63/LS 2883 system having originated from that OB association (see also Shannon et al 2014).…”
Section: Discussionsupporting
confidence: 56%
“…Our derived distance of 2.6 +0.4 −0.3 kpc is larger than the 2.3±0.4 kpc estimated by Negueruela et al (2011), but again consistent within the 1σ uncertainties. However, the distance estimate of Negueruela et al (2011) was based on the best previous determination of the distance to Cen OB1, which has recently been revised upwards to 2.6 ± 0.5 kpc (Corti & Orellana 2013). Hence our distance remains fully consistent with the PSR B1259−63/LS 2883 system having originated from that OB association (see also Shannon et al 2014).…”
Section: Discussionsupporting
confidence: 56%
“…The average color excess is E(b − y) = 0.29 (±0.03 sd; ±0.0041 se). These estimates are in perfect agreement with other authors (see Corti & Orellana 2013, and the reference therein).…”
Section: Distribution Of O-b9 Stars Toward Centaurussupporting
confidence: 93%
“…Corti & Orellana (2013) give the distance to the cluster as 1.9±0.5 kpc and the age of ∼15 Myr. Bonatto et al (2006) estimated the cluster's age as 14 ± 2 Myr and concluded that the star formation in NGC 4755 began ≈14 Myr ago and proceeded for about the same length of time.…”
Section: Wind-blown Energy Deposit Of the Most Massive Stars Within Gmentioning
confidence: 97%
“…At the same time, young star aggregates help us to probe the Galactic spiral structure, being one of the most prominent spiral arm tracers, together with gas, in the form of HI, HII, or CO (Carraro 2013 -see e.g. Shorlin 1 (Carraro & Costa 2009), Danks 1 and 2 (Baume et al 2009), NGC 6193/6167 (Baume et al 2011) or CenOB1/NGC 4755 (Corti & Orellana 2013). In this paper we extend our study to the remarkable IC 2944/2948 region, located at l ∼ 294.…”
Section: Introductionmentioning
confidence: 99%